2016
DOI: 10.1371/journal.pone.0153802
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Simulation of Three Dimensional Quantum Wires

Abstract: A method is presented to calculate the eigenenergies and eigenfunctions of quantum wires. This is a true three-dimensional method based on a direct implementation of the time-dependent Schrödinger equation. It makes no approximations to the Schrödinger equation other than the finite-difference approximation of the space and time derivatives. The accuracy of our method is tested by comparing it to analytical results in a cylindrical wire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The transmission characteristics of the MMI coupler can be determined using either the self-imaging theory or numerical methods such as the eigenmode method and beam probe method. This work employed two-dimensional FDTD numerical method instead to optimize and verify the designs of MMIs [32] as it was shown to produce sufficiently accurate results in simulating devices based on SOI channel waveguides. Device design for fabrication purpose was carried out using DW-2000 tool accessed through CMC Microsystems [33].…”
Section: Figmentioning
confidence: 99%
“…The transmission characteristics of the MMI coupler can be determined using either the self-imaging theory or numerical methods such as the eigenmode method and beam probe method. This work employed two-dimensional FDTD numerical method instead to optimize and verify the designs of MMIs [32] as it was shown to produce sufficiently accurate results in simulating devices based on SOI channel waveguides. Device design for fabrication purpose was carried out using DW-2000 tool accessed through CMC Microsystems [33].…”
Section: Figmentioning
confidence: 99%
“…Various parameters of the waveguides and heater element are given in Table 2. The top view of the MMI 1 and MMI 4 , and phase shifters MMI 3 and MMI 4 , calculated using MATLAB Mode Solver [18] as well as from FDTD simulation [19], and corresponding waveguide width and access waveguide positions to obtain single self-image at the output port. The device acts as two independent optical switches depending on whether the input is fed through a i1 (A) or a i2 (B)…”
Section: Thermo-optic Heatersmentioning
confidence: 99%
“…Electric field inside the (a) MMI 1 (input through port a i1 ) and (b) MMI 2 (input through port a i2 ). Two-dimensional FDTD numerical method was used to optimize and verify the design [19], as it was shown to produce sufficiently accurate results in simulating devices based on SOI channel waveguides.…”
Section: Field Distribution In the MMI Couplers /Decouplersmentioning
confidence: 99%
“…[7] The FDTD method benefits from being computationally efficient while being fully generalizable for solving the Schrödinger equation for arbitrary potentials in three dimensions.…”
Section: Appendix a A Finite Difference Time Domainmentioning
confidence: 99%
“…Our theoretical materials discovery program has found that the hyperpolarizability of a cylindrical nanowire with an aspect ratio of at least 10:1, which is attached to a permanent electric dipole with an inert spacer bridge, yields a first hyperpolarizability near the fundamental limit. The ideal configuration is found by varying the dipole strength and distance between the molecule and nanowire while calculating the off-resonant electronic response of an electron using the finite-difference time-domain (FDTD) technique [7]. While many theoretical models yield a hyperpolarizability near the limit, the system proposed here is within reach of modern nano-fabrication techniques.…”
Section: Introductionmentioning
confidence: 99%